Gene cloning : an introduction - Brown, T. A (Chapman and Hall, 1995)
The third edition of \"Gene Cloning\" is a fully revised and updated version of this introductory text on the subject. It is longer and contains greater detail, yet is still aimed at undergraduates and at those who have little or no previous experience of cloning techniques. There are two additions to the contents. The first is a chapter on the polymerase chain reaction, a technique that has assumed great importance in molecular biology. The second is a final chapter on plant genetic engineering, reflecting the increasing research interest, and general concern, in promoting environmentally sensitive practices in agriculture. It is in a larger format than previous editions and is printed in two colours. It should be of interest to first and second year life sciences undergraduates, especially those reading biochemistry, molecular biology, biotechnology, cell biology and medicine.
Keywords: genetické inženýrství; klonování organismů; Cloning, Organism; Klonování; genetika; Genetic Engineering; Genetics; genetika, lékařská genetika; Genetika